Implementation of the UTAUT2 Model with Gamification and Its Influence on Behavioral Intentions and Behavior of Use of M-Banking - Kefas Anugrah; Josua Partogi Parasian Pasaribu; Christina Dwi Astuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine how the influence of the UTAUT2 model along with gamification on behavioral intentions and behavior in using m-banking. The independent variables in this study are performance expectancy (PE), effort expectancy (EE), social influence (SI), hedonic motivation (HM), perceived value (PV), gamification (GM), facilitating conditions (FC), habit ( HB). The dependent variables in this study are behavioral intentions (BI) and use behavior (UB). The sample of this research is the community, users, and/or customers who use m-banking services in the Jakarta area. The sample of this study amounted to 200 respondents. The research method used is quantitative descriptive analysis. The results of this study indicate that perceived value (PV) and habit (HB) have a positive influence on behavioral intentions (BI). Then facilitating conditions (FC), habit (HB), and behavioral intentions (BI) have a positive influence on use behavior (UB). Meanwhile, performance expectancy (PE), effort expectancy (EE), social influence (SI), hedonic motivation (HM), gamification (GM), and facilitating conditions (FC) have no influence on behavioral intentions (BI).